Agro-transformation and evaluation of resistance to Phytophthora infestansin Solanum tuberosumL. variety Désirée - Orbegozo, Jeanette (2013)
The Oomycete Phytophthora infestans (Mont.) de Bary, the causal agent of the disease known as late blight, is primarily responsible for the decreased in production performance and potato crops worldwide. The integration of the complete Rgenes sequences in the potato genome using Agro-transformation appears an alternative to be considered in the fight against this pathogen. The Rpi-blb2 gene (Rgene) from the wild species Solanum bulbocastanumDunal shows a broad resistance to isolates ofP. infestans,making it an important candidate for plant breeding studies. This paper reports the integration of the Rpi-blb2gene into potato var. Désirée genome by Agrobacterium tumefaciens- mediated transformation system, the molecular characterization of 29 events transformed and whole plant infection with isolate POX67 of P. infestansfrom Peru. Désirée events [Rpi-blb2] 4 and Désirée [Rpi-blb2] 30, showed a substantial resistance to P. infestansinfection confirming complete transfer of the Rpi-blb2gene from a wild species to a cultivated species by genetic transformation.